The Lexicon of Argumentation for Argument Mining: methodological considerations - Patrick Saint Dizier (Anglophonia)
In this article, in contrast with numerous statistical approaches which show little interest for linguistic analysis, we propose methodological considerations aiming at identifying several categories of linguistic cues which are typical of argumentation and can be used for automatic argument mining within the framework of computational linguistics. These are elaborated from a corpus of arguments that was compiled for this study. An argument being a relation between a controversial statement (claim) and a support or an attack, we deal with the marks specific to each class and those related to the expression of the relations which hold between them. To conclude we propose an experimental model to evaluate the strength of each of these components. Some elements of an implementation and an evaluation are provided.